Analysis of the Effect of Service Quality Dimensions, Perceived Value, and Trust on Customers of Delivery Services through E-commerce - muhammad wahyu ariyanto; Rifelly Dewi Astuti (Jurnal Manajemen Industri dan Logistik, 2023)
The objective of this study was to examine the value of the influence of service quality dimensions, customer perceptions and beliefs on satisfaction in using delivery services. This research was conducted on selected shipping services via e-commerce in Indonesia with a total of 389 respondents. The novelty of this research lay in the social and economic conditions when the COVID-19 pandemic was still ongoing and according to government policies or calls for people to stay at home. This study concluded that the dimensions of assurance and empathy had a positive and significant effect directly and indirectly through trust on customer satisfaction, the tangible dimension only influenced customer satisfaction indirectly through trust. Meanwhile, the other two dimensions of service quality, namely responsiveness and reliability, did not affect customer satisfaction either directly or indirectly through trust. Trust could also mediate between the relationship between perceived value and customer satisfaction. It could be seen that it had an original sample value of 0.161 and a Pvalue of 0.000, which was smaller than 0.05.